Social ties, resources, and migrant labor contention in contemporary China : from peasants to protesters - Becker, Jeffrey (Lexington Books, 2014)
This book examines labor protest in authoritarian states through a study of the evolution of migrant labor protests in China over the past three decades. It explores the economic, political, and demographic changes that have influenced migrant labor protest activity, how migrant workers engage in protest today, and protest strategies they employ.